2012
DOI: 10.1002/ajim.22058
|View full text |Cite
|
Sign up to set email alerts
|

Work safety climate and safety practices among immigrant Latino residential construction workers

Abstract: Background Latino residential construction workers experience high rates of occupational fatality and injury. Work safety climate is an especially important consideration for improving the safety of these immigrant workers. This analysis describes work safety climate among Latino residential construction workers, delineates differences in work safety climate by personal and employment characteristics, and determines associations of work safety climate with specific work safety behaviors. Methods Data are from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…To promote safe behaviour on construction sites, previous researchers measured safety attitude [24], analysed the relationship between safety attitude and safety performance [25], and discussed how safety interventions could improve safety attitude and performance [26]. Mohamed et al found that workers' attitudes towards safety responsibilities and their risk perceptions explained their intentional behaviour [27].…”
Section: Tpb and Construction Safety Researchmentioning
confidence: 99%
“…To promote safe behaviour on construction sites, previous researchers measured safety attitude [24], analysed the relationship between safety attitude and safety performance [25], and discussed how safety interventions could improve safety attitude and performance [26]. Mohamed et al found that workers' attitudes towards safety responsibilities and their risk perceptions explained their intentional behaviour [27].…”
Section: Tpb and Construction Safety Researchmentioning
confidence: 99%
“…Supervisors' potential to engage in retaliation in the workplace and to affect workers' job opportunities is a concern among residential construction workers. 39 To estimate overall safety climate perception, a safety climate score ranging from 0 to 100% was calculated for each respondent based on their answers to the survey questions. The safety climate score was calculated as the proportion of answers that suggested a positive safety climate over the total number of responses (see Appendix 1 for questions and coding).…”
Section: Safety Climate Measurementioning
confidence: 99%
“…Our findings are in line with previous work showing Hispanic construction workers to be at risk of experiencing inadequate safety training. 2,39,[68][69][70] The general perception among survey respondents was that there is a need for increased fall prevention equipment, safety training, and clear safety roles and responsibility definition, and that management commitment to safety is undermined by a fear of retaliation and prioritizing productivity over safety. These factors point to a poor overall construction safety climate experienced by these workers and strong directions for improvement.…”
Section: Safety Climate Scale and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that safety was perceived as a joint responsibility of workers and management. Since then, many studies were conducted and revealed a significant positive association between safety climate and various aspects of occupational health and safety performance in the construction industry [5,[21][22][23] and subsequent safety behaviors among Latino residential construction workers, with differences by trade being particularly important [24]. Teo & Feng [25], in their study about safety culture in construction sites, found that safety climate has an impact on the three dimensions of safety culture, psychological, situational/environmental and behavioral dimensions.…”
Section: Construction Safety Climatementioning
confidence: 99%